The future of work: disciplined useful activity. Issue 3 (15th August 2019) - Cottey, Alan
Abstract : Purpose: The purpose of this paper is to draw attention to the importance of the current global ecological overload (GEO) for the future of work in the twenty-first century and to propose a new understanding of what work is. Design/methodology/approach: To achieve this purpose, the author uses qualitative methods to assess what is likely and what is possible. The author presents three broad-brush future scenarios, dubbed chaos, muddle and wisdom. The approach adopted depends on two basic normative principles, named Liveable Global Habitat and Necessities as of Right. Findings: The neoliberal commitment to economic growth is a driver for GEO. A liveable future requires a decisive turn away from neoliberal values. As part of this, the author proposes a new understanding of work, disciplined useful activity, which differs radically from the current understanding. "Useful" means contributing to two basic principles: to maintain and enhance a civilised human society and a liveable global habitat for a rich variety of species; and to accord to all people, as of right, in practice and not merely in name, the basic necessities of a civilised life. Social implications: AI and robots will probably continue to replace today's kinds of human employment. But this need not render any humans unemployed, whose work (in the new sense) will be wanted in, for two examples, caring (including self-care) and participatory democracy. Originality/value: This paper offers a contribution to the resolution of the current and anticipated problems of GEO and of disruptive technologies.